Deciding to Call the Shots: Awareness, Agency, and Shelter-Bbuilding During Home Birth Planning - (:unkn) unknown (My University, 2018)
The purpose of this dissertation was to explore the decision-making process for women who choose planned home birth. Medical studies suggest that there is a greater risk of perinatal death (3.9 vs. 1.8 deaths per 1,000 births) associated with planned home birth. There is professional disagreement about provision of home birth perinatal services and social and economic barriers to home birth. The percent of home births in the United States rose by 71 percent from 2004 to 2014, indicating the presence of elements other than risk and cost in the decision-making process for planned home birth. In this dissertation, I sought to gain insight into the reasons women exit the conventional perinatal care system and choose planned home birth. A grounded theory study, guided by the Theory of Emancipated Decision-Making, was conducted with eleven adult women who have planned a home birth in the United States with a Certified Nurse Midwife. Data were collected using semi-structured, in-depth interviews. Of the eleven women who chose planned home birth, nine gave birth at home and two transferred to the hospital under non-emergent conditions; all participants gave birth vaginally. Constant comparative analysis of interview data generated the Basic Social Process essential to the decision to plan a home birth, Calling the Shots. Calling the Shots explained how the women in this study solved the problem of decreased agency in their perinatal care. The theoretical explanation for deciding to plan a home birth centers around three core concepts: Realizing an Alternative, Deciding to Call the Shots, and Building a Shelter. Agency in perinatal care was the main influence for decision-making in this sample. This dissertation study generated three manuscripts: a qualitative literature synthesis, a grounded theory study, and a transfer policy case study. This dissertation and its manuscripts contribute to nursing’s understanding of the decision-making process for women who choose planned home birth. Understanding this process informs future research about the role of agency in other types of perinatal care. Understanding the multitude of ways agency is exercised by women during perinatal care may contribute to interventions for improved perinatal outcomes.
Keywords: decision-making; grounded theory; nursing; planned home birth; women's agency